2016
DOI: 10.1155/2016/8516748
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Superoxide Dismutase, Glutathione Peroxidase, and Peroxisome Proliferator Activated Receptor Gamma Polymorphisms on the Risk of End‐Stage Renal Disease among Han Chinese Patients

Abstract: Background. Single nucleotide polymorphisms (SNPs) of antioxidants, including superoxide dismutase 2 (SOD2) and glutathione peroxidase 1 (GPX1), play an important role in the risk for cancer and metabolic disorders. However, little is known regarding the effect of antioxidant SNPs on renal events. Methods. We prospectively enrolled multicenter patients with end-stage renal disease (ESRD) and those without chronic kidney disease (CKD) of Han Chinese origin, with SOD2 (Val16Ala), GPX1 (Pro197Leu), and PPAR-γ (Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…Heavy alcohol drinking can cause liver damage and activate intrinsic prothrombin activation pathway, especially in the ALDH2 lowexpression group. Chao et al have reported the interplay between superoxide dismutase genes and PPAR signaling [26]. In our study, the SOD2 high-expression group showed decreased PPAR signaling pathway (Table 2).…”
Section: Discussionsupporting
confidence: 59%
“…Heavy alcohol drinking can cause liver damage and activate intrinsic prothrombin activation pathway, especially in the ALDH2 lowexpression group. Chao et al have reported the interplay between superoxide dismutase genes and PPAR signaling [26]. In our study, the SOD2 high-expression group showed decreased PPAR signaling pathway (Table 2).…”
Section: Discussionsupporting
confidence: 59%
“…Today, the influence of polymorphisms rs1801282 of gene PPARG on oxidative processes and antioxidant is not in doubt. A recent study conducted by Chia-Ter Chao (2016) demonstrated Pro 12 →Ala association with increasing SOD activity in renal disease (P<0.028) [9]. We also found the intensification of LPO in carriers of alleles 12Pro in polymorphism Pro 12 →Ala of gene PPARG, whereas a significant decrease in activity of the enzyme catalase links AOC in patients with type 2 diabetes, was found as in the case of polymorphism Pro 12 →Pro of gene PPARG, and as in the presence of the allele 12Pro in this genotype [10].…”
Section: Introductionmentioning
confidence: 94%
“…In the pathogenesis of type 2 diabetes is activated by excessive formation of reactive oxygen species, leading to an intensification of LPO and oxidative stress, which takes a leading role in the development of complications [8][9][10]. Proved, that type 2 diabetes -a free radical pathology [3].…”
Section: Introductionmentioning
confidence: 99%
“…Certain SNP of the GPX1 gene is also found to increase the risk of renal events among patients with type 1 DM, and correlates with higher plasma ROS markers . Previously, we also discovered that TT genotype of exon 2 of the SOD2 gene (rs4880) conferred a significantly lower risk of presenting ESRD among patients without DM ( P = 0.014) . On the other hand, very few studies address the effect of antioxidant SNPs on the survival of ESRD patients.…”
mentioning
confidence: 99%